Abortion care preferences and trade-offs when traveling out-of-state for facility-based services: findings from a discrete choice experiment - Gracia Sierra; Klaira Lerma; Gabriela Alvarez Perez; Anitra Beasley; Kari White (BMC Health Services Research)
Abstract Background Pregnant people living in states that banned abortion after the US Supreme Court’s decision overturning Roe v Wade (Dobbs v Jackson Women’s Health Organization -Dobbs decision) may evaluate multiple factors when deciding where to obtain facility-based abortion care in another state. We examine Texans’ stated preferences for out-of-state facility-based abortion care and quantify the trade-offs they would make when choosing between out-of-state facilities following a 2022 abortion ban. Methods In August 2022, we surveyed Texans ≥ 16 years old seeking abortion at in-state facilities or who were searching online for information about accessing abortion care. We used a Bayesian discrete choice experiment to analyze 12 choice sets for out-of-state facility-based abortion care and to assess preferences for three care attributes: wait time to appointment, distance to facility, and cost. We estimated conditional, multinomial, and mixed logit models to examine respondents’ attribute preferences and how these differed across subgroups. We used marginal rates of substitution to express Texans’ tradeoffs in terms of willingness to pay and willingness to travel for different attributes. Results Among 136 respondents (1,362 observations), time to next appointment was the most important attribute (β = -0.887, p < 0.001), followed by cost (β = -0.006, p < 0.001) and distance (β = -0.001, p < 0.001). Respondents were willing to pay an additional $248 (95% CI: $220, $278) and travel 917 miles (95% CI: 711, 1123) further to get an appointment one week sooner. The willingness to pay for a one-week reduction in wait time to appointment was higher among respondents who did not report any economic hardships ($313, 95% CI: $255, $371) than among those who had one or more economic hardships ($175, 95% CI: $142, $208). Conclusion This discrete choice experiment examining Texans’ preferences for out-of-state facility-based abortion care demonstrates that people seeking abortion prioritize wait time to appointment when deciding where to obtain care. Efforts to make timely care a more feasible option for all those seeking abortion care are needed to mitigate the potential widening of disparities in access to care now that more states have banned abortion.